OC-125 Iron deficiency anaemia is a common presenting issue with giant paraesophageal hernia and resolves following repair. (28th May 2012) - Markar, S R; Carrott, P; Hong, J; Low, D
Abstract : Introduction: Giant Paraesophageal hiatal hernias (PEH) are most commonly associated with symptoms of chest pain, early satiety and GERD. However, Iron-deficiency anaemia is an under-appreciated condition associated with giant PEH. The aim of this study was to evaluate the incidence of iron-deficiency anaemia in a cohort of patients with giant PEH and assess the incidence of resolution associated with operative PEH repair. Methods: Between 2000 and 2010, 270 patients underwent operative repair of PEH and were prospectively entered into an IRB-approved database. From this cohort, 123 (45.6%) patients demonstrated a pre-existing diagnosis of iron-deficiency anaemia. 77 patients had a documented pre-operative haemoglobin level (Hb) consistent with iron-deficiency anaemia and a follow-up Hb level at least 3 months following surgery and constituted the study population. Results: From the cohort of 77 patients with documented pre-operative iron-deficiency anaemia, 72 (94%) underwent elective PEH repair, with a median age was 75 (range 39–91). Cameron erosions were endoscopically documented preoperatively in 25 patients (32%). The average preoperative Hb value was 11.8 (7.6–16). Postoperatively at 3–12 month follow-up, the average Hb level was 13.2 (10.7–17), and at more than 1 year follow-up it was 13.6 (9.2–17.2) (p<0.05). Furthermore 90% of patients had a rise in post-operative haemoglobin level by at least 1 g/dl. Anaemia was fully resolved postoperatively (Hb≥12.0 in females, ≥14.0 in males) in 55 (71%) patients. This resolution was observed more commonly in women (40/50, 80%) than men (15/27, 56%, p<0.05). Also younger patients (<70 years) were more likely to resolve their anaemia (29/33 vs 26/44; p<0.05) and have a greater post-operative Hb (14.0 vs 13.0 g/dl; p<0.05) than older patients. 40 patients required preoperative iron supplementation, 29 (73%) were able to discontinue iron following surgery. There was no significant difference in the resolution of anaemia in patients with or without Cameron erosions (19/25 vs 36/52, p=0.54). Conclusion: This single institution study shows a high incidence of iron-deficiency anaemia (45.6%) in patients with giant PEH. Elective repair results in resolution of the anaemia and discontinuation of iron supplementation therapy, in more than 70% of patients. This improvement in Hb is independent of the presence of pre-operative Cameron erosions. This study demonstrates the clinical and potential economic benefits of elective PEH repair of patients with Giant PEH and iron-deficiency anaemia. Competing interests: None declared.